Influence of seasons and sites on bioaerosols in indoor wastewater treatment plants and proposal for air quality indicators. (2nd September 2022) - Mbareche, Hamza; Dion-Dupont, Vanessa; Veillette, Marc; Brisebois, Evelyne; Lavoie, Jacques; Duchaine, Caroline
ABSTRACT: During wastewater treatment, bioaerosols are generated and, can either remain in suspension for several hours or settle on surfaces and workers may be exposed. The presence of pathogens in the air could contribute to an increased frequency of gastrointestinal or respiratory illness amongst workers. Due to harsh winter conditions in Eastern Canada, many of the steps in the wastewater treatment process occur indoors, leading to a greater risk of significant occupational exposure especially if there is inadequate ventilation or a lack of personal protection. This work has used stationary sampling at various indoor wastewater treatment steps both in winter and summer. Bioaerosols were evaluated using both culture and molecular methods along with ventilation characterization. Endotoxins were quantified, as well as total cultivable and gram-negative bacteria and pathogen indicators using qPCR. This study highlights the presence of potential pathogens at all steps in the treatment process, which may represent a potential occupational hazard. Comparisons between summer and winter data suggest that water temperature is an important factor for microbial activity and suggest that increasing the rate of air changes per hour in summer would be beneficial to reduce the concentration of bioaerosols during this time of the year. The screening, grit/FOGs removal and biofiltration were the most bioaerosol-loaded sites. Based on strong correlations, we suggest the reconsideration of exposure limits in WWTPs. Workers should be encouraged to use personal respiratory protection to limit the risk of health problems, especially during long-term work. Implications: The work presented herein showcases significant correlations between concentrations of endotoxins, cultivable bacteria, gram-negative bacteria, and total bacteria by qPCR from air collected in indoor wastewater treatment plants. These correlations lead us to propose new limit of exposure values, revisited to fit the endotoxin exposure limits recommendations. The results can serve as guidelines for future proposals for air quality indicators.